Evaluation of pharmacovigilance related knowledge, attitude and practice among healthcare professionals and students in a tertiary-care hospital: a cross-sectional study - Shanker, Shamili; Mohandas, Kalpana; Narayanan, G. Karthik; Thirumurthy, Ranjena; Balaji, Rajasekaran; Chalawadi, Manjunatha Hanumappa (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Pharmacovigilance (PV) plays a critical role in ensuring medication safety by identifying, evaluating and preventing adverse drug reactions (ADRs). Assessing the knowledge, attitude and practice (KAP) of healthcare professionals is essential for strengthening ADR reporting systems. To assess the knowledge, attitude and practice (KAP) related to pharmacovigilance among healthcare professionals and students and to analyse the association of KAP scores with age and professional category. Methods: This cross-sectional study utilized the ICMR pharmacovigilance KAP questionnaire to assess responses from 332 participants. Descriptive statistics were applied, Kruskal–Wallis’s test for intergroup comparison and Spearman’s correlation was used to evaluate associations between age and KAP scores. Data on professional experience were not available. A p value<0.05 was considered statistically significant. Results: The mean (±SD) knowledge, attitude and practice scores were 4.57±1.30, 3.20±0.74 and 4.29±1.46, respectively. Knowledge (H=9.68, p=0.046) and practice (H=9.83, p=0.043) differed significantly across professions. Age showed a very weak, non-significant correlation with knowledge (ρ=0.103, p=0.060) and no correlation with attitude (ρ=0.013, p=0.809), but a weak significant correlation with practice (ρ=0.188, p=0.0006). Conclusion: Participants demonstrated moderate knowledge and practice scores with overall positive attitudes. Knowledge and practice varied significantly across professions, while attitude did not. Age showed only weak associations with KAP domains. These findings indicate the need for profession-specific pharmacovigilance training, particularly to strengthen knowledge and practice among students and nursing staff.